2019
DOI: 10.1158/1078-0432.ccr-18-1811
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Neuroblastoma by T Cells Redirected with an Optimized GD2-Specific Chimeric Antigen Receptor and Interleukin-15

Abstract: Purpose: A delay in encountering the cognate antigen while in the circulation, and the suboptimal costimulation received at the tumor site are key reasons for the limited activity of chimeric antigen receptor-redirected T cells (CAR-T) in solid tumors. We have explored the benefits of incorporating the IL15 cytokine within the CAR cassette to provide both a survival signal before antigen encounter, and an additional cytokine signaling at the tumor site using a neuroblastoma tumor model. Experimental Design: We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(135 citation statements)
references
References 41 publications
7
124
0
2
Order By: Relevance
“…Thirdly, immune monitoring in this phase 1 study indicated a correlation between circulating IL-15 levels and GD2 CAR T cell expansion [89]. Circulating IL-15 levels could not only potentially be used as a biomarker for CAR T cell expansion, but a pre-clinical xenograft mouse model transduced with GD2 CAR T cells overexpressing IL-15 also showed improved expansion, enhanced anti-tumor activity and improved survival [93].…”
Section: Adoptive Cell Therapymentioning
confidence: 74%
See 1 more Smart Citation
“…Thirdly, immune monitoring in this phase 1 study indicated a correlation between circulating IL-15 levels and GD2 CAR T cell expansion [89]. Circulating IL-15 levels could not only potentially be used as a biomarker for CAR T cell expansion, but a pre-clinical xenograft mouse model transduced with GD2 CAR T cells overexpressing IL-15 also showed improved expansion, enhanced anti-tumor activity and improved survival [93].…”
Section: Adoptive Cell Therapymentioning
confidence: 74%
“…Infused cells can be isolated from PB [82][83][84][85], as well as from tumor tissue (e.g., TILs) [8,20]. In addition, isolated cells can be genetically modified to improve recognition of tumor cells, for example through knock-in of a NBL-specific T cell receptor (TCR) [40,86,87], a chimeric antigen receptor (CAR) [20,[88][89][90][91][92][93][94][95], or a bispecific antibody [96,97] against tumor specific targets such as GD2, PRAME, NY-ESO-1, L1-CAM, B7-H3, and mutated ALK. Very low or even absent surface expression of major histocompatibility complex I (MHC-I) on NBL cells has led to the focus on MHC-I unrestricted ACT-strategies, mainly exploiting NK cell-and CAR therapy (or a combination of both).…”
Section: Adoptive Cell Therapymentioning
confidence: 99%
“…51 Further engineering will improve the efficacy of GD2-CAR-T, for example by coexpression of IL15. 52 Moreover, GD2-CAR-T effector function might be enhanced with additional immune checkpoint blockade. 53 In conclusion, we report for the first time, that GD2directed immunotherapy by GD2-CAR-T can prevent metastasis formation in a highly aggressive model of TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the emergence of "Armored CARs" that constitutively secrete cytokines such as IL-12. IL-15 and IL-18 also provided further hope that more sophisticated engineering of CAR-T cells can overcome the persistence issue all together ( Figure 1B) [70][71][72][73].…”
Section: Strategies To Improve Carsmentioning
confidence: 99%